New record of Distimake ternifoliolus (Pittier) A.R.Simões & Staples (Convolvulaceae Juss.) from the Brazilian savanna reveals its disjunct distribution pattern - Rodrigues, Leonardo de S.; de Sousa, Izaias C. [UNESP]; Figueiredo, Marlene F.; Santos, Francisco D. S. (Pensoft Publishers, 2024)
We present the first record of Distimake ternifoliolus (Pittier) A.R.Simões & Staples (Convolvulaceae) from the Brazilian savanna (Cerrado). This is a rare species, previously known only from the savannas of the Venezuelan Llanos and the Guianas. We provide a key characters, data on geographic distribution, habitat, conservation status, flowering and fruiting period, updated distribution maps and a key for Distimake Raf. species from Ceará.
Keywords: Creepers; Disjoint distribution; Pleistocene; Savanna enclaves